Tru64 UNIX troubleshooting : - Moore, Martin L. (Digital Press, 2003)
Dealing with system problems—from user login failures to server crashes--is a critical part of a system administrator’s job. A down system can cost a business thousands of dollars per minute. But there is little or no information available on how to troubleshoot and correct system problems in most cases, these skills are learned in an ad-hoc manner, usually in the pressure-cooker environment of a crisis